Can secondary osteons be used as ontogenetic indicators in sauropods? Extending the histological ontogenetic stages into senescence. Issue 2 (6th February 2017) - Mitchell, Jessica; Sander, P. Martin; Stein, Koen
Abstract: Sauropod bone histology has provided a great deal of insight into the life history of these enormous animals. However, because of high growth rates, annual growth rings are not common in sauropod long bones, so directly measuring growth rates and determining sexual maturity require alternative measures. Histological ontogenetic stages (HOS) have been established to describe the changes in bone histology through development for basal Macronaria and Diplodocoidea, and subsequently for Titanosauria. Despite this, the current HOS model is not able to discriminate bone tissues in late ontogeny, when sauropods had reached asymptotic size and continued to live into senescence but their long bones became extensively remodeled by secondary osteons and all primary bone was destroyed. Here we establish remodeling stages (RS) to characterize the Haversian bone development through ontogeny in eight sauropod taxa (Apatosaurinae, Giraffatitan brancai, Camarasaurus spp., Dicraeosaurus spp., Ampelosaurus atacis, Phuwiangosaurus sirindhornae, Magyarosaurus dacus, and Alamosaurus sanjuanensis ) and find significant correlation of RS with corresponding femur length (CFL) for the studied taxa, with the exception of Dicraeosaurus and Magyarosaurus . Remodeling stages are based on the maximum number of observable generations of crosscutting osteons from the innermost, mid-, and outermost part of the cortex. The correlation with CFL indicates that secondary osteons present an ontogenetic signal that could extend the histological ontogenetic stages. Remodeling stages also provide additional insight into the changes in histology through ontogeny for Sauropoda. This method has the potential to be used in other taxa, such as thyreophorans and many ornithischians, that develop Haversian tissue through development.